The Retention–Replacement Dilemma: A Capital Budgeting Perspective on Aging Industrial Assets - Gunawan, Yulison Tri; Mahastanti, Linda Ariany (Arbain Publishing, 2025)
This study examines the decision to replace an aging palletiser machine using discounted cash flow (DCF) analysis, employing standard corporate metrics such as Net Present Value (NPV), Internal Rate of Return (IRR), and Discounted Payback Period (DPP). The analysis demonstrates that replacing the machine results in a positive NPV of approximately IDR 2.80 billion, an IRR of 25.8% that exceeds the company’s WACC of 11.2%, and a discounted payback period of about six years. These results remain favorable even under realistic perturbations, such as a ±20% change in maintenance escalation and ±2 percentage points in WACC. Retaining the machine, with escalating maintenance costs and a compressed Mean Time Between Failures (MTBF), would only be beneficial under highly unlikely conditions, such as near-flat wear-out rates or negligible downtime costs. The replacement decision provides a clear value proposition for shareholders by minimizing long-term operational risks, such as unpredictable downtime and increasing maintenance expenses. Additionally, the study highlights the importance of using a super-linear escalation model for late-life maintenance costs, which more accurately reflects the growing costs associated with aging assets. The findings support a repeatable approach to capital budgeting decisions, offering companies a robust framework for resolving similar “repair or replace” dilemmas across their asset base. Ultimately, the study concludes that replacing the aging palletiser maximizes shareholder value, aligns with corporate policy thresholds, and remains a sound investment even in the face of potential uncertainties in the operational environment.